Leadership for Environmental Sustainability. - Redekop, Benjamin W. (Routledge Studies in Business Ethics, 2010)
Explores the connection between leadership and sustainability from various disciplinary perspectives, including sociology, history, psychology, business, literature, communication, and the arts. This book is suitable for scholars, practitioners, students, and educated readers.